A Fresh Start for Stigmatized Groups: The Effect of Cultural Identity Mindset Framing in Brand Advertising. Issue 5 (20th October 2021) - Milfeld, Tyler; Haley, Eric; Flint, Daniel J.
Abstract: The idea that individuals can create a new beginning, known as the fresh start mindset, is deeply embedded in American culture. This mindset represents an accessible, shared construct that may be particularly relevant for changing attitudes toward two highly stigmatized groups: ex-offenders and drug addicts. While previous advertising literature has suggested that ambiguous or symbolic approaches may help improve consumer response, we show (using four studies) that cultural identity mindset framing (CIMF) can generate more positive affect toward the sponsoring brand and more positive attitudes toward the stigmatized group. Study 1 shows that explicitly referencing a highly stigmatized group leads to a less positive affective response toward the brand. Study 2 reveals that CIMF improves that response. Study 3 uses a real brand to replicate the positive affect toward the sponsoring brand. Study 4 documents a positive attitude shift toward the stigmatized group. Our research opens a new research corridor for explicitly referencing a stigmatized group, expands the stigmatized group discourse to two underrepresented groups, provides empirical evidence for the fresh start message frame, and answers a call to understand whether corporate social responsibility advertising is better than not advertising it at all.